Association Between Convenience of Transportation and Unmet Healthcare Needs of Rural Elderly in Korea - Youngeun Choi; Kiryong Nam; Chang-yup Kim (Journal of Preventive Medicine and Public Health)
Objectives In rural areas of Korea, where public transportation infrastructure is lacking and alternative systems are poor, the elderly experience inconveniences in using healthcare, although their need is high. This study aimed to analyze the association between the convenience of transportation and unmet healthcare needs among the rural elderly. Methods The data used were collected in the 2016 Community Health Survey among rural elderly individuals aged 65 or older. Dependent variable was the unmet healthcare needs, explanatory variable was the convenience of transportation. The elderly were divided into 3 groups: with no driver in the household, with a driver, and the elderly individual was the driver (the self-driving group). Covariates were classified into predisposing, enabling, and need factors. They included gender, age, education, income, economic activity, household type, motor ability, subjective health level, number of chronic diseases, anxiety/depression, and pain/discomfort. The data were analyzed using logistic regression and stratification. Results A significant association was found between the convenience of transportation and unmet healthcare needs. When examined unadjusted odds ratio of the group with a driver in the household, using the group with no driver as a reference, was 0.61 (95% confidence interval [CI], 0.54 to 0.68), while that of the self-driving group was 0.34 (95% CI, 0.30 to 0.38). The odds ratios adjusted for all factors were 0.69 (95% CI, 0.59 to 0.80) and 0.79 (95% CI, 0.67 to 0.91). Conclusions We confirmed a significant association between inconvenient transportation and unmet healthcare needs among the rural elderly even after adjustment for existing known factors. This implies that policies aimed at improving healthcare accessibility must consider the means of transportation available.